Intersubjectivity in dialectic master and slave of Hegel - Farha, Mohammad; Mohammad, Batol (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This paper discusses the nature of Intersubjectivity in the dialectic master and slave of the German philosopher Hegel. Intersubjectivity is an important philosophical subject; it occupies an important place in the humanities in general, such as psychology, sociology, etc. Although the term "Intersubjectivity" is a contemporary term, that is not new, so we can say that we will follow it from Descartes’s famous phrase, "I think if I exist." To be the beginning of a range of questions and treatments and philosophical research, Singles and individualism. The importance of this research is that it is a philosophical study of the structure, its concept and its implications in Hegel’s philosophy, as a basic law for understanding the nature of the relationship between the selves and its role in the process of consciousness. This is evident in the German philosopher Hegel through his famous "master and slave" argument. This study seeks to understand the nature of others in Hegel, and to show the levels of the relationship between the ego and the other by focusing on the study of the dialectic of the master and the slave, and the role of feminism in the concept of freedom in an attempt to understand the true meaning of consciousness from the philosophy of Hegelian.